Effect of hemodynamic parameters on physiological blood flow through cardiovascular disease (CVD) – the perspective review - Nur Afikah, Khairi @ Rosli; Mohd Azrul Hisham, Mohd Adib; Nur Hazreen, Mohd Hasni; Mohd Shafie, Abdullah (Akademi Baru, 2020)
One of the cardiovascular diseases (CVD) that affect the heart is coronary artery disease (CAD). CAD is the disease that leads to fetal death due to plaque formation which blocked blood that carries oxygen to the human body. The tremendous trends of death in cardiovascular disease become worrisome to cardiologists and medical practitioners. Thus, many researchers grab the initiative to study the cardiovascular hemodynamic parameters such as wall shear stress (WSS), blood velocity, endothelial shear stress (ESS), and strain rate in identifying coronary artery disease factors. This paper aims to investigate the hemodynamic parameters that lead to the formation of coronary artery disease and the effect of the parameters on the physiological blood flow. Few research papers were investigated and analyzed by comparing numerical data and images from CFD analysis. Based on the study, the main hemodynamic parameter that produced the formation of coronary artery disease are wall shear stress and related proportionally with velocity, shear stress, and strain rate factors. The result shows the low wall shear stress (WSS) developed the high formation of plaque in the coronary artery and will develop stenosis in an artery leading to a decrease of lumen size and increase of velocity near the plaque region. In conclusion, the evolutions of computational hemodynamic study are bringing huge contributions in identifying coronary artery disease and show a significant relationship with physiological blood flow.